Comparison of childhood cancer survivors' nutritional intake with US dietary guidelines. Issue 8 (24th March 2015) - Zhang, Fang Fang; Saltzman, Edward; Kelly, Michael J.; Liu, Shanshan; Must, Aviva; Parsons, Susan K.; Roberts, Susan B.
Abstract Background Despite improved survival, childhood cancer survivors experience significantly elevated risk of premature mortality and serious morbidity due to chronic health conditions. Poor diet quality can exacerbate chronic health conditions in the survivors but their nutritional intake has not been adequately studied. Procedure We assessed the Healthy Eating Index 2010 (HEI‐2010) in 22 survivors of pediatric acute lymphoblastic leukemia and lymphoma (median age = 11.7 years) and compared survivors' dietary intake to the 2010 Dietary Guidelines for Americans. Dietary data were collected using repeated 24 hr dietary recalls over a 1‐year period, which were averaged to estimate habitual intake. Results The mean HEI‐2010 in childhood cancer survivors was 52.7, about 50 percent of the maximum score. Long‐term survivors (time from diagnosis ≥10 years) had a significantly lower HEI‐2010 than recent survivors (time from diagnosis <5 years) (β = −11.5, 95% CI: −22.1, −0.9, P = 0.047). For individual food groups and nutrients, survivors had a particularly poor adherence to green vegetables and beans, total vegetables, and whole fruits. None of the survivors met the guidelines for dietary fiber and potassium intake. Only 4%, 19%, 24%, and 29% met the guidelines for vitamin D, sodium, calcium, and saturated fat intake. The average intake in relative to the recommended intake was 32% for vitamin D, 50% for potassium, 63% for fiber, and 85% for calcium, but was 115% for saturated fat and 143% for sodium. Conclusions Childhood cancer survivors, in particular long‐term survivors, have a poor adherence to the US dietary guidelines. Pediatr Blood Cancer 2015;62:1461–1467. © 2015 Wiley Periodicals, Inc.